Noms propres de territoires algériens : lieux de revendications et de conflits géoculturels, sociohistoriques et linguistiques - BOUALILI, Ahmed (Journal of Human Sciences, 2016)
The power of the name is recognized in all societies. Communities that it describes as "primitive" make use in the rituals of magic, but also to define their hunting territories. In the so-called "modern" societies, things have hardly changed: the name is also used to exercise a power to the individual; at the community level, it was decided to give to sites where they are appreciated by the political project of the dominant group names. He does not hesitate to change the names of places for a world as their beliefs and its prospects. This change is driven by historical, psychological and linguistic factors. Thus, a primary function of designation, the toponym has been graft a symbolic function that reflects the dominant group projects.